Personal Branding KPH. Purbodiningrat Sebagai Anggota Dewan Perwakilan Rakyat Daerah Istimewa Yogyakarta - Anggita Sarasati; Susanne Dida; Aat Ruchiat Nugraha (Program Studi Magister S2 Ilmu Komunikasi Hindu Institut Agama Hindu Negeri Gde Pudja Mataram, 2023)
Popularity does not guarantee that others will know the individual. One of the politicians is KPH Purbodiningrat, who was only considered to have taken advantage of the popularity and title he had as the advantage that he had as a mantu ndalem of the Yogyakarta Palace when he was a member of the DPRD-DIY. The purpose of this research is to discover the identity that KPH Purbodiningrat wants to show, the efforts made in building and maintaining personal branding, and the performance and achievements obtained while being a member of the DPRD-DIY. This research uses a post-positivistic paradigm with a qualitative approach and case study research type. The data obtained in this study were through observation, interviews, online data searches, and literature study. The result from this research is identity shown by KPH Purbodiningrat is that it still holds the cultural value of the privilege of Yogyakarta. It looks conservative because it keeps cultural values. However, this conservative's values can only be seen from his values ​​and ideology till he keeps. In carrying out activities and other activities, KPH Purbodiningrat can adapt to the environment and the times. His activities are cut up into online and offline, and the performance and achievements obtained by KPH Purbodiningrat are not only in the realm of members of the DPRD-DIY but also outside the role of members of the DPRD-DIY. The conclusion of this study conclude that the identity shown by KPH Purbodiningrat is as a member of the DPRD-DIY who has adaptive conservative. The advice given from the results of research in strengthening personal branding can emphasize the value of communicating messages by using jargon, as well as by utilizing social media. The consistency of messages must be the highlight and monitoring and evaluation of content and news in social media.